The Security Implications Of The Employment Of Foreign Workers Holding Visit Pass (Temporary Employment) In Peninsular Malaysia - Mohamad Fauzi Md Isa; Nik Azmi Nik Omar; Arbaiyah Jusop; Sahubar Ibrahim Ismail Gani; Rodziana Mohamed Razali; Hendun Abd. Rahman Shah; Intan Nadia Ghulam Khan; Nisar Mohammad Ahmad; Muhammad Safwan Ibrahim; Norailis Ab Wahab (Institute of Public Security of Malaysia (IPSOM), 2024)
Migration policy is an essential component in the country’s national security agenda. History shows that internal security and threats to security are the primary logic that informs foreign worker policy in Malaysia. This article looks into the security implications of the employment and presence of foreign workers holding the Visit Pass (Temporary Employment) or ‘PLKS’ holders in Peninsular Malaysia. This study is part of an overarching research that reevaluates a number of employment policies applicable to PLKS holders and assesses the impact of employment policies and practices that concern this category of workers from both public order and human security perspectives. It used qualitative methods such as desk review, focus group discussions (FGD) and round table discussions (RTD), and is based on the Security and Public Order Policy (DKKA 2019) and the intent to develop a comprehensive foreign worker policy. Areas assessed include the involvement of foreign workers in crimes, the phenomenon of irregularity, terrorism, corruption, infectious diseases, drug abuse and drug trafficking.